2020
DOI: 10.1002/jper.19-0283
|View full text |Cite
|
Sign up to set email alerts
|

Is the personalized approach the key to improve clinical diagnosis of peri‐implant conditions? The role of bone markers

Abstract: BackgroundStudy objectives were 1) to estimate diagnostic capacity of clinical parameters, receptor activator of nuclear factor kappa‐B (RANKL) and osteoprotegerin (OPG) to diagnose healthy peri‐implant condition (HI), peri‐implant mucositis (PIM) and peri‐implantitis (PIMP) by assessing respective diagnostic accuracy, sensitivity, specificity and diagnostic ranges 2) to develop personalized diagnostic model (PDM) for implant monitoring.MethodsSplit‐mouth study included 126 patients and 252 implants (HI = 126,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…Peri-implantitis has been described as a pathological condition that occurs in functionally loaded tissues that surround dental implants and is characterized by mucosal inflammation and progressive marginal bone loss ( 15 ). The clinical features of peri-implantitis are enlarged periodontal pockets and bleeding from probing ( 16 ). It has been reported that blade-type implants are encapsulated with fibrous tissue, which has been proposed as a determinant of implantation failure due to the micromotion induced in the implant by the prosthesis ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Peri-implantitis has been described as a pathological condition that occurs in functionally loaded tissues that surround dental implants and is characterized by mucosal inflammation and progressive marginal bone loss ( 15 ). The clinical features of peri-implantitis are enlarged periodontal pockets and bleeding from probing ( 16 ). It has been reported that blade-type implants are encapsulated with fibrous tissue, which has been proposed as a determinant of implantation failure due to the micromotion induced in the implant by the prosthesis ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, in spite of the conflicting data that have evidenced the morphological and immunophenotypical differences between peri‐implantitis and periodontitis, the former has shown to be more severe in inflammatory infiltrate 7 . In this sense, peri‐implantitis has demonstrated an increase in bone turnover markers, pro‐inflammatory cytokines, such as tumor necrosis factor or interleukin‐1, and proteinases, considered as valid and accurate molecules to monitor peri‐implant disorders 8‐10 …”
Section: Introductionmentioning
confidence: 99%
“…7 In this sense, peri-implantitis has demonstrated an increase in bone turnover markers, pro-inflammatory cytokines, such as tumor necrosis factor or interleukin-1, and proteinases, considered as valid and accurate molecules to monitor peri-implant disorders. [8][9][10] Therefore, the purpose of the present preclinical in vivo study was to assess the colonization and shifts in microbiota and host-derived biomarkers in the course of ligature-induced and spontaneous progression of peri-implantitis in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…
Recent data show that the correct management of periodontitis and peri-implantitis represents a potential challenge in the health system [1,2]. Periodontal disease and peri-implantitis are multifactorial diseases with infectious aetiology which, following an important immune response of the host [3,4], culminating in the progressive loss of supporting tissues, alveolar bone and finally determine the loss of the tooth or of the implant [5] and that affect patients' quality of life [6 -8]. However, in addition to these conditions, the morphostructural alteration of the stomatognathic system's hard and soft tissues can be determined by teeth extraction, trauma, prosthetic restorations [9] oral tumors, and pathological conditions such as severe dental or skeletal malocclusions [10,11].
…”
mentioning
confidence: 99%
“…Recently, efforts have been made in recent years to predictably stimulate true bone regeneration of periodontal tissues by introducing bioactive models or constructing patientspecific bone substitutes or growth factors [5,35].…”
mentioning
confidence: 99%